Jesus As A Special Messiah - Pangeran Manurung (Theological Journal Kerugma, 2020)
The problem in this essay lies in the issue of the Messiahship of Jesus which is thought to contain defects. Jesus is deemed unworthy of the title "Messiah" because his profile does not match the description of the Messiah in the Old Testament. The writing of this article aims to compare the concept of Messianic Judaism and its unique fulfillment in Jesus. The method used is a literature study of texts about the Messiah in the Old and New Testaments and relates them to Jesus' profile as the Messiah. As a result, Jesus as the Messiah in the New Testament did not meet the expectations of Judaism because Jesus presented a unique or different profile of Messiahship. The conclusion of this paper covers two things. First, Jesus as the Messiah must be understood from the Eschatological aspect. Second, the profile of Jesus' Messiahship is unique and goes beyond the "Messiahic" tradition of Judaism.